Jaringan Patologis dan Jenis Perforasi yang Menyebabkan Gangguan Pendengaran Konduktif pada Otitis Media Supurativa Kronis - Shantika Putra, Aditya; Sudarmanto, Yohanes; Wahyudiono, Ahmad Dian; Handoko, Edi (PERHATI-KL, 2025)
Background: Chronic Suppurative Otitis Media (CSOM) is an inflammatory middle ear condition that often leads to conductive hearing loss. Purpose: To analyse the correlation between pathological tissue and the type of perforation with conductive hearing loss, in patients with CSOM. Method: Cross-sectional study on medical records data of CSOM patients who visited the Ear, Nose, and Throat (ENT) outpatient clinic at Saiful Anwar General Hospital, between January 2019 and June 2022. The collected data included physical examination of the ear, audiometry results, and surgical findings during the operation. Comparative analysis was performed to compare audiometry results based on the pathological tissue diagnosis and the perforation type. Result: A total of 51 CSOM patients were included in the study. Moderate conductive hearing loss was the most common type (49% of cases). The comparative analysis showed no significant correlation between pathological tissue or the type of perforation with conductive hearing loss, in patients with CSOM. Conclusion: In this study, there were no significant corrrelation between pathological tissue and the type of perforation with conductive hearing loss in patients with CSOM.